Little witch academia - Yoshinari, Yoh. (2018)
"Reach out your hand, and your story will begin!" Those words changed young Atsuko "Akko" Kagari forever, sparking in her a lifelong dream of becoming a real witch. Now she's been accepted to the same school as her childhood hero, Shiny Chariot-the prestigious Luna Nova Witchcraft Academy. As the only student to come from a non-magical family, Akko finds herself surrounded by prodigies from around the world, but giving up isn't in her vocabulary. Whether it's making friends, proving the doubters wrong, or just flying on a broom, Akko is going to make her fantasy a reality!